ACCULTURATION OF HADRAH WITH TRADITIONAL MALAY PERCUSSION IN ARBAIN'S MAULID ACTIVITIES IN MEDAN - Muhammad Habibur Ridho; Vanesia Amelia Sebayang; Pulumun P Ginting (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This research is entitled "Acculturation of Hadrah with Traditional Malay Percussion in Maulid Arbain Activities in Medan City". The main purpose of this study is to identify the form of Hadrah performance in Maulid Arbain activities, analyze the Hadrah playing technique that is acculturated with traditional Malay music, and examine the acculturation process as a whole. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation, and is analyzed based on acculturation theory. The object of the research was focused on the performance of Hadrah in the Maulid Arbain activity at the Darul Ibtihaj Islamic Boarding School, Medan City. The results of the study show that there is an acculturation process between Hadrah and traditional Malay percussion music, as seen in the similarity of musical instruments such as tambourine and marwas to Malay drums. Acculturation is also reflected in interlocking-based game techniques that combine Hadrah rhythmic patterns with the peculiarities of Malay rhythms. In addition, the involvement of participants from various backgrounds, such as entrepreneurs, students, and Malay percussion music practitioners who study Hadrah, shows that this acculturation process also forms a dynamic and inclusive space for culturalinteraction in the community. This research found that Hadrah performance art during the Maulid Arbain celebrations in Medan City has undergone a significant acculturation process with traditional Malay music. This process is evident not only in the use of instruments such as the tambourine, bass hadrah, and marwas, but also in the playing techniques, which feature rampak and interlocking rhythmic patterns synonymous with Malay percussion music. Furthermore, the involvement of participants from diverse backgrounds, including the general public, demonstrates that Hadrah has become a platform for inclusive cultural expression. This acculturation enriches the aesthetic and spiritual values ​​of Hadrah performances, without diminishing the Islamic religious identity that underpins the performances. The acculturation of Hadrah with Malay music occurs not only musically but also socially—uniting Islamic boarding schools and the community within a single, dynamic cultural space. The polyrhythms created by the interlocking techniques serve as a musical symbol of the meeting of two major traditions that complement and enrich each other. This research provides several suggestions that can serve as a foundation for various parties to support the continuity and development of Hadrah art, which has undergone a process of acculturation with local culture, particularly in Medan City. This recommendation is aimed at further researchers, artists, educational and cultural institutions, and local governments that have a strategic role in preserving cultural and religious values.  Keywords: hadrah, acculturation, Malay music, interlocking, Maulid Arbain, Medan